Critical Thinking Skills of Students in Solving Mathematical Problem - Ardi Dwi Susandi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Mathematical critical thinking skills are one of the essential skills in the 21st century. However, in reality, many students still do not have good mathematical critical thinking skills. This is because the teacher has not been able to process students' critical thinking in mathematics. Most teachers only teach mathematical concepts without seeing how the students' critical thinking processes in solving mathematics problems are given. Therefore, it is necessary to know how the critical thinking process of students so that teachers know what strategies should be applied in the classroom. This study aims to (1) describe the critical thinking skills of students in Grade 8 in solving a system of linear equations in two variables (SLETV) and (2) identify the components of critical thinking in students. It is a study with a qualitative descriptive approach. Three indicators are used as the basis, namely analyzing, evaluating, and drawing a conclusion. As many as 32 subjects were involved (14 males and 18 females). The research instrument was a test with three problems containing three indicators. Data were collected through test and interview methods, and triangulation was done to compare the outcomes between tests and interviews. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that: (1) critical thinking skills of students are classified 'low'; (2) students' ability in concluding, as one indicator of critical thinking skills, is lower than other indicators.